The methodological structure of a language A to language B translation textbook - Yermolovich, Dmitry (English Studies at NBU, 2015)
The paper is based on the author’s experience of writing a Russian-English translation textbook and looks into the methodology of teaching students to translate into their non-mother tongue (language B). It is argued that a textbook delivering a course on general, rather than specialized, translation should move away from the popular format of text samples followed by glossaries and comments. Instead, the primary focus should be made on the utterance as the principal unit of translation. Utterances need to be analysed in terms of the situations which they reflect and their semantic class components (objects, events, abstracts, and relations). This approach, termed semantic-situational, can help make the learning and teaching of Language A to Language B translation more consistent and streamlined.